Kualitas Melon Hidiroponik dengan Penggunaan Media Tanam dan Dosis Pemberian Unsur Magnesium - Suhadi Sapto Yuwono; Hasan Basri (Balai Pelatihan Pertanian Jambi, 2021)
Improving quality of melons can be through by hydroponic cultivation, especially the hydroponic fertigation system. In fertigation system, fertilizer is given by gradually dropping in the substrate media so that roots can absorb nutrients quickly. Planting media as a place to support plants and nutrients are absorbed are known have effect to plant growth. While magnesium is an element that forms chlorophyll. A quality melon is characterized by its smooth, flawless skin, standard weight, and sweet taste. The purpose of this study was to determine the effect of using planting media and adding magnesium to the quality of melons. The results showed that the treatment of cocopeat and husk charcoal had a significant effect on the height of the melon plant, while the addition of Mg 10 g had a significant effect on the height and volume of melon. Treatment of planting media and the addition of magnesium did not significantly affect to the amount of dissolved solids (brix) of melons.